2023
DOI: 10.1109/tnb.2022.3156077
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Detection Using Colorimetric Plasmonic Sensors: A Proof-of-Concept Computational Study

Abstract: Traditional molecular techniques for SARS-CoV-2 viral detection are time-consuming and can exhibit a high probability of false negatives. In this work, we present a computational study of SARS-CoV-2 detection using plasmonic gold nanoparticles. The resonance wavelength of a SARS-CoV-2 virus was recently estimated to be in the near-infrared region. By engineering gold nanospheres to specifically bind with the outer surface of the SARS-CoV-2 virus, the resonance frequency can be shifted to the visible range (380… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Herewith, we show the performance of a portable SPR sensor (Figure 1a) using a direct detection scheme for SARS-CoV-2 using VHH-72-Fc bioreceptors (Figure 1b) referring to VHH-72 fused to a human IgG1 Fc domain by a GS(GGGGS)2 linker, as reported by Wrapp et al 17 The sensing platform is competitive with other optical sensing platforms recently described and developed. 37,38 Despite the nanomolar affinity of VHH-72 for the SARS-CoV-2 RBD reported by SPR, 17 the rapid dissociation is believed to effect negatively the SPR read out. The bivalence of VHH-72-Fc, due to the Fc domain of human IgG1 genetically linked by a HHHHHHRENLYFQG linker to the VHH domain (Figure 1), results in nanomolar affinity constant of K D = 1.5×10 -9 M with a k on of 1.2×10 5 M -1 s -1 and an improved k off equal to 1.8×10 -4 s -1 , as determined by the portable P4 SPR (Affinité Instruments) instrument (Figure 2a).…”
Section: Sensors and Diagnostics Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Herewith, we show the performance of a portable SPR sensor (Figure 1a) using a direct detection scheme for SARS-CoV-2 using VHH-72-Fc bioreceptors (Figure 1b) referring to VHH-72 fused to a human IgG1 Fc domain by a GS(GGGGS)2 linker, as reported by Wrapp et al 17 The sensing platform is competitive with other optical sensing platforms recently described and developed. 37,38 Despite the nanomolar affinity of VHH-72 for the SARS-CoV-2 RBD reported by SPR, 17 the rapid dissociation is believed to effect negatively the SPR read out. The bivalence of VHH-72-Fc, due to the Fc domain of human IgG1 genetically linked by a HHHHHHRENLYFQG linker to the VHH domain (Figure 1), results in nanomolar affinity constant of K D = 1.5×10 -9 M with a k on of 1.2×10 5 M -1 s -1 and an improved k off equal to 1.8×10 -4 s -1 , as determined by the portable P4 SPR (Affinité Instruments) instrument (Figure 2a).…”
Section: Sensors and Diagnostics Accepted Manuscriptmentioning
confidence: 99%
“…The sensing device is competitive with other optical sensing platforms recently described and developed. 37,38 By engineering gold nanospheres to distinctively bind with the outer surface of the SARS-CoV-2 virus, the resonance frequency was adjusted to the visible range (380–700 nm). It was shown that the broadband absorption of the virus merges with the visible spectrum when the virus is partially covered with gold nanoparticles at a specific coverage percentage and this feature can be used in efficient and accurate colorimetric plasmon sensors for COVID-19 detection.…”
Section: Introductionmentioning
confidence: 99%
“…They also serve as signal amplifiers in photothermal-based sensing platforms, converting near-infrared light into localized heat upon binding to viral antigens. Furthermore, they showed potential in colorimetric assays, where color changes indicated the presence of viral components (Baidya & Hassan, 2022;Wang et al, 2022). Gold nanocages, characterized by their porous structure, were functionalized with probes for sensitive and selective detection of viral components.…”
Section: Gnps: Shining Beacons In Covid-19 Diagnosticsmentioning
confidence: 99%
“…Gold nanocages, characterized by their porous structure, were functionalized with probes for sensitive and selective detection of viral components. For instance, they were coated with DNA probes that recognized the SARS-CoV-2 spike protein, allowing rapid and specific detection (Baidya & Hassan, 2022). Gold nanocages enhanced the sensitivity and specificity of PCR-based assays by acting as signal amplifiers.…”
Section: Gnps: Shining Beacons In Covid-19 Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation